2020
DOI: 10.1097/brs.0000000000003597
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Comprehensive Geriatric Assessment on Early Postoperative Complications Following Lumbar Spinal Stenosis Surgery

Abstract: Study Design. Prospective cohort study. Objective. The aim of this study was to evaluate the predictive value of comprehensive geriatric assessment (CGA) for early postoperative complications in elderly patients (aged 65 years or older) following lumbar spinal stenosis surgery. Summary of Background Data. CGA is a multidisciplinary evaluation modality proven to be effective in various fields of geriatrics. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…In addition, the number of deficit domains in CGA before treatment and the quality of life were correlated 40 . Several previous studies have reported that the cumulative number of deficits in CGA is an independent predictor of surgical outcomes in elderly patients undergoing elective surgery 8,9 . In a previous study, which is consistent with our study, the presence of two or more deficits in the preoperative CGA was associated with major postoperative complications in elderly patients who underwent colorectal cancer surgery 7 …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, the number of deficit domains in CGA before treatment and the quality of life were correlated 40 . Several previous studies have reported that the cumulative number of deficits in CGA is an independent predictor of surgical outcomes in elderly patients undergoing elective surgery 8,9 . In a previous study, which is consistent with our study, the presence of two or more deficits in the preoperative CGA was associated with major postoperative complications in elderly patients who underwent colorectal cancer surgery 7 …”
Section: Discussionsupporting
confidence: 89%
“…However, in this study, all the elderly patients were classified as ASA II or III, and the ASA classification did not show any significant association with major postoperative complications. Similar results were also observed in previous studies on elderly patients who underwent surgery for either spinal stenosis or colon cancer 8,44 . ASA class II includes mild to moderate systemic disease, and ASA class III includes a severe disease process that limits activity 45 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Frailty is characterized by physiological age-related decreases in energy, cognitive function, physical health, and other deficits that collectively make the patient more vulnerable to stressors, resulting in adverse outcomes [ 4 , 6 , 17 ]. Consensus on how best to define and measure frailty remains elusive [ 1 , 2 , 5 ]. Frailty has been measured using different methods in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of CGA in improving surgical outcomes has been proven by RCTs in other medical domains [120,121]. Chang et al [76] developed CGA for surgical spine patients. The scale covers most comprehensively the concept of frailty and showed significant correlation with postoperative complications in a prospective cohort [76].…”
Section: Candidate Scales For Preoperative Assessmentmentioning
confidence: 99%